Efektifitas Penggunaan Metode Talking Stick dalam Pembelajaran Tamrin Kelas I Reguler Marhalah Tsanawiyah TMI Pi Al-Amien Prenduan tahun 2021 - Sherly Quraisy; Asmaniyah Asmaniyah (Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
The purpose of this research is to see how effective the talking stick method is for learning Tamrin class I Marhalah Tsanawiyah TMI Putri Al-Amien Prenduan. This research uses quantitative and experimental research methodologies in a single class. The researcher employed a pretest in this procedure. This research's population consisted of regular first-class female students, totaling 221 female students, with a sample of 10% of the population, namely regular class I students